(untitled) (Jurnal Mu’allim, 2026)
Abstract This study examines the relevance of educational hadiths regarding teaching methods to the new curriculum implemented by the Indonesian Ministry of Religious Affairs,namely the Love-Based Curriculum (KBC). This study aims to describe how the hadiths that have existed since the time of the time of the Prophet Muhammad (peace be upon him) remain relevant and suitable for use and application in the field of education, particularly Islamic Religious Education; to analyze the meaning and content contained in educational hadiths regarding teaching methods; and to analyze how the teaching methods found in the hadiths can be applied in a learning context. This study is a qualitative study using a descriptive qualitative approach. The primary data sources in this study are books on educational hadiths, the Ministry of Religious Affairs of the Republic of Indonesia’s Love-Based Curriculum Guide, as well as Sahihal-Bukhari and Sahih Muslim. Meanwhile, the secondary data sources in this study are relevant articles, books, or journals. The results of this study indicate that tarbawi hadiths regarding teaching methods are highly relevant and suitable for use and application in the learning process.This demonstrates that the second source of Islamic religious teachings, namely the Hadith, can be applied as a guideline in the learning process, even though the writing of hadiths itself has existed since the time of the Prophet Muhammad. Abstrak Penelitian ini mengkaji tentang relevansi hadis-hadis tarbawi tentang metode mengajar dengan kurikulum baru yang diterapkan oleh Kementerian Agama Indonesia, yaitu Kurikulum Berbasis Cinta atau KBC. Penelitian ini bertujuan untuk mendeskripsikan bagaimana hadis-hadis yang sudah ada sejak zaman Rasulullah SAW masih relevan dan cocok untuk digunakan dan diterapkan dalam dunia pendidikan, khususnya Pendidikan Agama Islam, menganalisis maksud dan kandungan yang ada dalam hadis tarbawi tentang metode mengajar, serta menganalisis bagaimana metode mengajar yang ada dalam hadis dapat diterapkan dalam sebuah pembelajaran. Penelitian ini merupakan penelitian kualitatif dengan jenis studi pustaka (library research) dan penyajian data secara deskriptif. Sumber data primer dalam penelitian ini adalah buku-buku hadis tarbawi, Panduan Kurikulum Berbasis Cinta Kementerian Agama Republik Indonesia, serta Ṣaḥīḥ al-Bukhārī dan Ṣaḥīḥ Muslim. Sedangkan sumber data sekunder dalam penelitian ini adalah artikel, buku, atau jurnal yang relevan. Hasil dari penelitian ini menunjukkan bahwa hadis-hadis tarbawi tentang metode mengajar sangat relevan dan cocok untuk digunakan dan diterapkan dalam pembelajaran. Hal ini menunjukkan bahwa sumber ajaran agama Islam yang kedua, yaitu hadis, dapat diterapkan sebagai pedoman dalam pembelajaran, meskipun hadis itu sendiri sudah ada sejak zaman Rasulullah SAW.